Declaración - Hardt, Michael, 1960-; Negri, Antonio, 1933- (Pensamiento crítico (Akal Editor), 2012)
This is not a manifesto. Manifestos provide a glimpse of a world to come and also call into being the subject, who although now only a specter must materialize to become the agent of change. Manifestos work like the ancient prophets, who by the power of their vision create their own people. Today's social movements have reversed the order, making manifestos and prophets obsolete. Agents of change have already descended into the streets and occupied city squares, not only threatening and toppling rulers but also conjuring visions of a new world. More important, perhaps, the multitudes, through.